Chronic participation in externally paced, but not self-paced sports is associated with the modulation of domain-general cognition. Issue 8 (14th September 2019) - Ballester, Rafael; Huertas, Florentino; Pablos-Abella, Carlos; Llorens, Francesc; Pesce, Caterina
Abstract: The present study investigated the role of chronic sport participation in the modulation of vigilance and inhibitory control. We also aimed to disentangle the relative contribution of different types of sport expertise and sport-related fitness to the exercise-cognition relationship. Three groups of young adults differing in their chronic sport expertise (externally-paced sports, n  = 22, self-paced sports, n  = 22, non-athletes, n  = 22) took part in the study. Participants completed a cardiovascular fitness test, a hand-eye coordination test and two different types of vigilance tasks: (1) Psychomotor Vigilance Task (PVT) and (2) Oddball Task, which were designed to gain insight into the cognitive processes involved in sustaining attention over time and allocating selective attention by exerting inhibitory control, respectively. No differences were found in PVT performance between the two athlete groups and between self-paced sports athletes and non-athletes, whereas athletes from externally-paced sports outperformed non-athletes. Crucially, athletes from externally-paced sports also differed from those of self-paced sports and non-athletes in the Oddball task, showing less omission and commission errors. The sport expertise effect was independent of participant's cardiovascular fitness while hand-eye coordination modulated vigilance and inhibitory control performance. Our findings add novel empirical evidence to the role of expertise in cognitively demanding sports as an important factor in the relationship between exercise and cognition.